Clinical outcomes of adenoid cystic carcinoma of the head and neck: a single institution 20-year experience. Issue 7 (8th June 2016) - Ali, S; Yeo, J C-L; Magos, T; Dickson, M; Junor, E
Abstract: Background: This study reports the clinical outcomes of head and neck adenoid cystic carcinoma treatment over a 20-year period. Methods: The treatment outcome of 51 head and neck adenoid cystic carcinoma patients treated between 1992 and 2013 were analysed. Patients were stratified into radical treatment and disease control groups. Results: A total of 40 patients underwent surgery and post-operative radiotherapy. The 10-year disease-specific survival rate was 93 per cent. Eleven patients had tumour recurrence: of these, nine were pulmonary metastases. The 11 patients in the disease control group had a median follow up of 21 months (range, 2–172 months); 5 underwent radical radiotherapy with palliative intent. Conclusion: There was late tumour recurrence in over 25 per cent of patients. Adenoid cystic carcinoma has a high tendency to relapse even after radical excision and adjuvant therapy. However, definitive radiotherapy should still be considered on an individual basis because it may provide local control and prolong patient survival.